Parental human investment: economic stress and time allocation in Russia - Bruckauf, Z (2013)
A decade of growth and wealth generation in Russia ended in 2009 with the collapse in GDP and rising unemployment. This Great Recession added new economic challenges to the ‘old’ problems facing children and families, including widening income inequalities and the phenomenon of social orphanage. One question is how the new and existing material pressures affect parent–child relationships. This research contributes to the answer by examining, in aggregate terms, the role poverty plays in the allocation of parental time in this emerging economy. Utilising a nationally representative sample of children, it explores how child interactions with parents are affected by aggregate and idiosyncratic shocks. Drawing on the rational choice paradigm and its critique, we put forward the Parental Time Equilibrium as an analytical guide to the study. This theoretical approach presents individual decisions concerning time spent with children over the long term as the product of a defined equilibrium between resources and demands for involvement. We test this approach through pooled cross-sectional and panel analyses based on the Russian Longitudinal Monitoring Survey dataset from 2007 to 2009. Children in low-income households face the double disadvantage of a lack of money and time investments at home, with both persistent and transient poverty being associated with lower than average parental time inputs in the sample. Moreover, while on average, we find that children do maintain the amount of time they spend with their parents under conditions of severe financial strain, low–income children lose out on play time with the mother. Material resources cannot be considered in isolation from structural disadvantages, of which rural location in particular is detrimental for parent–child time together. The study demonstrates that the cumulative stress of adverse macro-economic conditions and depleted material resources makes it difficult for parents to sustain their human investment in children. The evidence this study provides on the associations between economic stress and pa-rental time allocations advances our knowledge of the disparities of in the childhood experience in modern Russian society. The findings strongly support the equal importance of available resources and basic demand for involvement, thus drawing policy attention to the need to address both in the best interests of children.